L’‘inconsueta ricostruzione’ di Copenaghen - Beretta, Ilaria (Scienze del Territorio, 2015)
This paper suggests that the City of Copenhagen’s experience as a case of “restoration of the city” is in some way different and original compared to what we think could be intended with this expression. In fact, in the Danish Capital, the municipal administrators and citizens regained the feeling of belonging to and loving the city not because of a ‘naive’ relationship with nature, but, on the contrary, because of a wider and smarter use of the best available technologies. In this sense, modernization is not an enemy of the environment but, on the contrary, it is a supporter because it uses the advantages of progress (i.e. better efficiency, reduced use of resources, etc.) in order to improve environmental protection. As a result, it is our opinion that Copenhagen represents a very interesting case of co-evolution between socio-economic development, technological progress and environmental protection which, through smart integration of area policies, are all heading in the same direction, namely sustainability.